Green Economy and Green Jobs Development in Indonesia - Ahmad Ma‟ruf; Lula Farahdita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
The utilization and development of environment-friendly renewableenergy are becoming increasingly important given the increasinglylimited fossil energy sources or non-renewable energy sources. Theproblem in this study is how to develop a Green Job in support ofrealizing Green Energy in Indonesia.This study is qualitative researchwith descriptive analysis. Green Energy is one step to realize a GreenEconomy. In practice, the required human resources also support and inline with the context of the Green Economy and Green Energy, i.e.Green Jobs. Development opportunities Green Jobs in the energy sectoris very large, but the phenomenon of Green Jobs in Indonesia is stillrelatively new, therefore the participatory processes in policydevelopment and implementation that supports it is absolutelynecessary, and also with the promotion.